Nightfall - Asimov, Isaac, 1920-1992.; Silverberg, Robert (New York : Doubleday, 1990)
Kalgash is a world on the edge of chaos, torn between religious fanaticism and scientific rationalism. Their civilization is threatened by Nightfall, the first sunset in over two thousand years.
"A Foundation book.".
Kirkus Review.
School Library Journal.
Wilson's Fiction.
Adult.
Adult
Keywords: Science fiction; Science fiction